The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/j.2048-7940.2004.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Support Groups

Abstract: Support groups have become a part of the lives of many people who suffer from illness and injury. Physicians and other healthcare professionals often recommend them to patients and families dealing with medical conditions, and many support groups are diagnosis specific. The members of five support groups were surveyed to determine the factors that influenced their decision to participate. They reported they attended the groups to meet others with the same diagnosis and to gain more information about the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…Our findings are consistent with studies amongst young people with diabetes and disability which describe how membership of support groups enabled opportunities for bonding with others similar to themselves, and how this increased a sense of belonging . In studies of adults’ with a wide variety of conditions including allergy, cancer, stroke, diabetes, and physical disabilities, benefits of patient groups are also consistent with our findings suggesting that irrespective of the underlying condition or age, support groups appear to promote a sense of community, acceptance and emotional benefit, increased self‐confidence and a decrease in isolation . Previous research has found that supportive networks lead to decreased engagement in risky behaviours, increased knowledge regarding management and an increase in treatment adherence and positive behaviours .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with studies amongst young people with diabetes and disability which describe how membership of support groups enabled opportunities for bonding with others similar to themselves, and how this increased a sense of belonging . In studies of adults’ with a wide variety of conditions including allergy, cancer, stroke, diabetes, and physical disabilities, benefits of patient groups are also consistent with our findings suggesting that irrespective of the underlying condition or age, support groups appear to promote a sense of community, acceptance and emotional benefit, increased self‐confidence and a decrease in isolation . Previous research has found that supportive networks lead to decreased engagement in risky behaviours, increased knowledge regarding management and an increase in treatment adherence and positive behaviours .…”
Section: Discussionsupporting
confidence: 91%
“…Reduced social interaction and social isolation is common after TBI and has a significant impact on quality of life (Dahlberg et al, 2006;Hoofien, Gilboa, Vakil, & Donovick, 2001;McDonald et al, 2008;Struchen et al, 2011;Temkin, Corrigan, Dikmen, & Machamer, 2009). Consistent with previous research, this study reinforces the value of the social interactions and support that groups can provide (Charles et al, 2007;Fleming et al, 2009;Fraas et al, 2007;Nilsson et al, 2011;Parente & Stapleton, 1999;Purk, 2004;Rodgers et al, 2007;Sargeant et al, 2000;Schulz, 1994;S. Schwartzberg, 1994;Straits-Troster et al, 2013;Vandiver & Christofero-Snider, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Results of these studies were generally consistent with each other, and with findings of other quantitative and mixed-method studies. These concluded that group interventions provided opportunities for social interaction and support (Charles et al, 2007;Fleming et al, 2009;Fraas et al, 2007;Nilsson et al, 2011;Parente & Stapleton, 1999;Purk, 2004;Rodgers et al, 2007;Sargeant et al, 2000;Schulz, 1994;S. Schwartzberg, 1994;Straits-Troster et al, 2013;Vandiver & Christofero-Snider, 2000), and could provide opportunities to simulate real world interactions (Knis-Matthews et al, 2006;Lundqvist et al, 2010;Newman & Newstadt, 2009;Niemeier et al, 2010;Sargeant et al, 2000;Smalley et al, 2007;Vandiver & Christofero-Snider, 2000).…”
Section: Examination Of Clinician Perceptions Of Group Therapy Intervmentioning
confidence: 99%
“…Social capital, on the other hand, can also increase people’s chances to accumulate health-relevant cultural capital, for instance through informal access to health information, expert knowledge and advice. Memberships in networks or social groups such as patient’s organisations, neighbourhood initiatives and self-help groups have been found to improve health knowledge 41 42. Thus the acquisition of health-relevant cultural capital is in major parts directly dependent on the availability of other types of resources, namely economic and social capital.…”
Section: Cultural Capital: Interactions and Transformations Relevant mentioning
confidence: 99%